Development and performance investigation on solar-powered thermoelectric radiant cooling in building-integrated system for a bedroom under hot and humid climate - Jarumongkonsak, Pornput (2016)
In order to replace a conventional air-conditioner (AC) based on vapour compression technology that directly has high global warming potential and also currently consumes the most fossil fuel primary energy in building sector of tropical countries for generating thermal comfort on sleeping purpose, other alternative green space cooling technologies, as thermoelectric cooling (TEC), has to be improved to have same performance with AC. This research aims to develop and investigate a performance of Solar-powered Thermoelectric Radiant Cooling (STRC) system, as the combination of TEC and radiant cooling (RC) that is well known in its low energy consumption advantage. The studies were conducted through calculations, CFD simulations, system performance simulations and experiments. The results of optimum STRC system design was proved to provide better thermal and air quality performances, while the result in energy performance was depended on the TEC’s COP and vapour condensation prevention. After novel developing of TEC’s cooling channel with combined helical and an oblique fin to induce effective secondary flows that highly reduced the TEC’s hot side temperature in this research, the COP was able to increase up to 175%. Meanwhile, a novel bio-inspired combined superhydrophobic and hydrophobic coating on RC panel were able to competently repel most condensed water droplets, leaving just tiny droplets that was hard to be seen by naked eye. Finally, the COP of STRC system from house model experiment in 1:100 scales under hot and high humid climate was as high as 2.1 that helped STRC to consume electricity 34% less than AC system. Along with other benefits, as no working fluid, noise-free and low maintenance needs, the return of investment (ROI) was studied to be only 5-6 years when being operated with grid electricity and 17-18 years with PV panel generated electricity.